DERMATOGLYPHIC PATTERN IN RELATION TO ABO, RH BLOOD GROUP AMONG MEDICAL STUDENTS - Shrivastava, Mohit; Jain, Ankit Pandey; Agarwal, Rahul; Vishwakarma , Ashish Kumar (Journal of Forensic Medicine and Toxicology, 2023)
Dermatoglyphics provides a scientific method foridentification of an individual and it is constant and sametill demise. Fingerprint evidence is undoubtedly play animportant role during identification of criminals,biometric, aadhar card, etc. In Modern Era, fingerprintsbecomes an effective method of identification and inpresent study an attempt has been made to analyse theircorrelation with gender, ABO & Rh blood group of anindividual. The present study was conducted among themedical students of Mahatma Gandhi Memorial MedicalCollege, Indore, India. Total 194 students were selected(107 male and 87 female) within age group of 19-28 years.Fingerprint patterns (loops, whorls, and arches) was takenusing the INK method and blood data were collected. Onconclusion, 38.65% of subjects belong to B blood groupfollowed by O, A and AB where 94.32% subject havingRh-positive. Loops were higher in both male & female.Among the subject of different blood groups, blood group‘A’ showed highest loops (Rh positive 62.19%), bloodgroup ‘O’ showed highest Whorls (Rh positive 45.88%and Arches were least common ranging from 9.32% (in“B” positives) to 5.29% (in “AB” positives). All suchparameters may help in using fingerprints as an importantfactor in Gender, ABO & Rh blood group determinationwhich enhancing the authenticity of finger-prints indetection of crime and criminals.
Keywords: ABO blood group; Arches; Dermatoglyphics; Loops; Rh blood group; Whorls